Changes in dietary intake, plasma carotenoids and erythrocyte membrane fatty acids in breast cancer survivors after a lifestyle intervention: results from a single‐arm trial. Issue 4 (21st January 2019) - Buckland, G.; Travier, N.; Arribas, L.; del Barco, S.; Pernas, S.; Zamora, E.; Bellet, M.; Cirauqui, B.; Margelí, M.; Muñoz, M.; Tusquets, I.; Arcusa, A.; et al.
Abstract: Background: The influence of nutrition on breast cancer prognosis is still inconclusive and therefore dietary interventions incorporating dietary biomarkers are needed to confirm compliance with dietary goals and clarify biological mechanisms. The present study assessed whether a lifestyle intervention in breast cancer survivors could affect dietary biomarkers of fruit and vegetables and fatty acids. Methods: In this phase II single‐arm trial, 37 overweight/obese early stage breast cancer patients completed a 12‐week diet and exercise intervention. The intervention involved 1‐h weekly diet sessions delivered by a dietician and 75‐min bi‐weekly physical activity sessions of moderate‐to‐high intensity led by trained monitors. Before and after the intervention, three 24‐h dietary recalls were carried out to calculate nutrient intakes and, in addition, blood samples were taken to measure plasma carotenoids, vitamin E and retinol concentrations and erythrocyte membrane fatty acid (EFA) composition. Wilcoxon signed rank tests were used to assess changes in dietary and biomarkers measurements over the intervention period. Results: After the intervention, there was a significant increase in the intake of dietary carotenoids (+15.1% compared to baseline) but not plasma carotenoids levels (+6.3%). Regarding the EFA levels, we observed a significant decrease in percentage of saturated fatty acids (−1.4%) and n ‐6 polyunsaturated fatty acids (−2.9%) and an increase in monounsaturated fatty acids (1.7%) and total and long‐chain n ‐3 polyunsaturated fatty acids (by 13.1% and 13.7%, respectively). A favourable decrease in the ratio of long‐chain n ‐6 to n ‐3 polyunsaturated fatty acids (−9.1%) was also observed. Conclusions: After a short‐term diet and exercise intervention in overweight/obese breast cancer survivors, we observed significant changes in dietary nutrients and fatty acid biomarkers, suggesting positive dietary changes that could be relevant for breast cancer prognosis.